Iron-binding by dissolved organic matter in the Western Tropical South Pacific Ocean (GEOTRACES TONGA cruise GPpr14) - Mahieu, Léo; Whitby, Hannah; Dulaquais, Gabriel; Tilliette, Chloé; Guigue, Catherine; Tedetti, Marc; Lefevre, Dominique; Fourrier, Pierre; Bressac, Matthieu; Sarthou, Géraldine; Bonnet, Sophie; Guieu, Cécile; et al. (Frontiers in Marine Science, 2024)
Iron (Fe) is an essential micronutrient for phytoplankton growth, but its scarcity in seawater limits primary productivity across much of the ocean. Most dissolved Fe (DFe) in seawater is complexed with Fe-binding organic ligands, a poorly constrained fraction of dissolved organic matter (DOM), which increase Fe residence time and impact Fe bioavailability. Here, we present the conditional concentration (L Fe ) and binding-strength (log K F e ' L c o n d ) of Fe-binding ligands in the Western Tropical South Pacific (WTSP) Ocean during the GEOTRACES TONGA cruise (GPpr14). The transect crossed the Lau basin, a region subject to shallow hydrothermal Fe inputs that fuel intense diazotrophic activity, the oligotrophic South Pacific gyre, and the Melanesian basin. Organic speciation was analyzed by competitive ligand exchange adsorptive cathodic stripping voltammetry (CLE-AdCSV) using salicylaldoxime at 25 µM. We found a high mean L Fe of 5.2 ± 1.2 nMeqFe (n = 103) across the entire transect, predominantly consisting of intermediate strength L2 ligands (84%; mean log K F e ' L c o n d of 11.6 ± 0.4), consistent with humic-like substances. DFe correlated with the humic-like component of the fluorescent DOM (HS-like FDOM), yet the electroactive Fe-binding humic-like substances (L FeHS ) accounted for only 20 ± 13% of L Fe in the mixed layer and 8 ± 6% in deep waters. Ligands were in large excess compared to DFe (mean excess ligand eL Fe = 4.6 ± 1.1 nMeqFe), suggesting poor stabilization of DFe inputs. High L Fe (up to 9 nMeqFe) in samples close to hydrothermal sites could be due to detoxification strategies from plankton communities toward hydrothermally-fueled toxic trace metals other than Fe, with an apparent dilution of the DOM from the Lau basin into neighboring regions. We also observed a different peak potential of the Fe salicylaldoxime complex detected by CLE-AdCSV between the Lau and Melanesian basins, and between surface and deep waters. To our knowledge, this change in potential has not previously been reported; whether this represents a novel detection of specificities in DOM composition merits further investigation. Competition between Fe and competing metals for ligand binding sites could favor DFe oxidation and precipitation near hydrothermal vents and explain the absence of strong Fe stabilization in the WTSP.